The performance of Textile Reinforced Concrete (TRC) panels under high-velocity impact load - Esaker, Mohamed (2025)
In recent decades, there has been a growing interest in the performance of buildings and infrastructure when subjected to severe loading conditions. Due to the fact that concrete is a material that is frequently employed in the construction industry, its performance under severe loading conditions, such as impact loading, has been the subject of multiple investigations. Concrete structures may experience localised impact from small, high-velocity projectiles resulting from blast-induced fragments or flying objects produced by forces of nature such as tornadoes or volcanoes. These missiles exhibit significant variations in their shapes and sizes, as well as in their velocities, stiffness, and orientation upon impact. Consequently, they cause a diverse range of damage to the structure. When concrete structures are subjected to high-velocity impact loading, small fragments can be generated from the back face spalling due to the low tensile strength of concrete. As a result, of the impact event, these fragments have the potential to move at a high velocity, which poses a risk to the safety of the occupants of the structure as well as those who are in the surrounding area. Therefore, improving the strength of concrete elements can reduce the hazards related to debris and thereby reducing the local damage. Conventional concrete can behave in various different ways when subjected to severe loading according to its brittle characteristics, tensile strength, and capacity to absorb energy. Thus, it is necessary to investigate new types of protective materials with the tensile capacity and ductility to absorb the impact energy and therefore resist high-velocity impact loads. This research aims to investigate the performance of textile-reinforced concrete (TRC) panels under high-velocity impact loading. The research method is comprised of a laboratory experimental and numerical programme to investigate varying parameters on the impact performance of TRC panels. In the experimental part, a comprehensive experimental programme was performed to investigate the effect of different influential parameters (e.g., strength of concrete, velocity of projectile, and type of textile) on the impact performance of TRC panels. A hundred and eight control and TRC panels were subjected to high-velocity impact loads from a non-deformable hemispherical steel projectile, which was fired from a compressed air gun, travelling with initial impact velocities ranging from ∼60 m.s-1 to ∼160 m.s-1. The effect of flexural toughness on impact resistance was also investigated by testing fifty-four control and TRC beams under a four-point bending test. Numerical analysis was performed using Abaqus/CAE software. The models were first validated and compared with the experimental results, and then a parametric study was conducted to identify the effect of different design parameters such as compressive strength of concrete, tensile strength of textile, thickness, and grid spacing of textile on the impact resistance of concrete panels. The results obtained from the parametric analysis were employed to develop an empirical model to predict the penetration depth of TRC panels under high-velocity impact loading on the basis of the empirical formula proposed by the US National Defence Research Committee. In the last phase of this research, a comparative investigation of six diverse machine learning models, including Decision Tree (DT), Extreme Gradient Boosting (XGB), Support Vector Machine (SVM), Random Forest (RF), K-Nearest Neighbours (KNN), and Adaptive Boosting (ADB) was performed with the aim of optimising for developing an accurate predictive model to predict the penetration depth of concrete panels subjected to high-velocity projectile impact loading. The models combined the experimental results of 195 samples based on experimental results obtained from this research and the literature.